Sequence Variation and Phylogenetic Relationships Among Ten Iraqi Rice Varieties Using RM171 Marker - Al-kazaz, Abdul Kareem (Iraqi Journal of Science, 2023)
In the present study rice microsatellite marker (RM 171) was used to evaluate the genetic diversity and determining cultivar identity among ten rice varieties (oryza sativa L.) (Seven local and three commercial varieties). PCR technique was performed using two specific primers. The result showed presence of a band (305bp) DNA sequencing was done to PCR product to detect sequence variation between the ten rice varieties. In order to detect the relationship among all varieties, alignment of RM171 marker sequence was carried out for each variety. Amber and Daawat varieties showed the highest similarity with 98% identity, while the difference (2%) consists of two gaps and two transition mutations (T/C) and (C/T). Furthermore, Amber was aligned with mashkhab-1; 6% variation was noticed includes 5% gaps of 16 nucleotides which are not found in Amber that distributed in four different locations. In addition to the gaps, two transversion mutations were identified (G/C) and (G/T). Phylogenetic relationships among varieties were achieved, which showed that genetic distances were ranged from 0.029 to 1.999 among rice varieties. Cluster analyses grouped the ten varieties into five main clusters depending on their geographic origin, their ancestor and their aroma characteristics and this revealed relatedness between aromatic and non -aromatic with few of independent varieties. The result of this study could be helpful in the future for rice breeding programs